Reiterated Commemoration: Hiroshima as National Trauma - SAITO, Hiro (Institutional Knowledge at Singapore Management University, 2006)
This article examines historical transformations of Japanese collective memory of the atomic bombing of Hiroshima by utilizing a theoretical framework that combines a model of reiterated problem solving and a theory of cultural trauma. I illustrate how the event of the nuclear fallout in March 1954 allowed actors to consolidate previously fragmented commemorative practices into a master frame to define the postwar Japanese identity in terms of transnational commemoration of "Hiroshima." I also show that nationalization of trauma of "Hiroshima" involved a shift from pity to sympathy in structures of feeling about the event. This historical study suggests that a reiterated problem-solving approach can be efficacious in analyzing how construction of national memory of a traumatic event connects with the recurrent reworking of national identity, on the one hand, and how a theory of cultural trauma can be helpful in exploring a synthesis of psychological and sociological approaches to commemoration of a traumatic event, on the other.